The pain stethoscope: A clinician$1 (Bs guide to measuring pains - Jensen, Mark P.; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2011)
n/a
1. Introduction -- 2. Measuring Pain Intensity -- 3. Measuring Pain Quality -- 4. Measuring Pain Location -- 5. Measuring pain behavior -- 6. Measuring pain interference -- 7. Measuring sleep quality -- 8. Measuring depression -- 9. Measuring general physical functioning -- 10. Measuring alcohol and drug use -- 11. Measuring global improvement and satisfaction with pain care -- 12. References.
Keywords: Medicine; Anesthesiology; Family medicine; Neurology; Pain Medicine; Emergency medicine; Medicine & Public Health; Anesthesiology; General Practice / Family Medicine; Neurology; Medicine/Public Health, general; Primary Care Medicine; Pain Medicine